JOB ENRICHMENT AND EMPLOYEE SATISFACTION IN FAST FOOD RESTAURANTS IN PORT HARCOURT, RIVERS STATE (American Journal of Pedagogical and Educational Research, 2025)
The study investigated job enrichment and employee satisfaction in fast food restaurants in Port Harcourt, Rivers State. A total number of 152 employees were carefully chosen from eight selected fast food restaurants in Port Harcourt, Rivers State. Three measures of job enrichment were tested to guide the study. Descriptive survey design was applied with the aid of random sampling method. The sample size for this study was 110 employees discovered through Taro Yamane’s formula. Copies of questionnaire were circulated to the respondents for the purpose of collecting data. Primary and secondary data were adopted for the study. Research instrument used for data collection for this study, was a questionnaire which was designed to accommodate five-point likert scale stated as: strongly agree 5(SA), agree 4(A), neutral 3(N), disagree 2(D), strongly disagree 1(SD). Data collected were analyzed using descriptive statistics and spearman rank correlation statistics. The findings revealed that there was positive significant relationship between task significance and employee satisfaction in fast food restaurants in Port Harcourt, Rivers State. The researcher concluded that all the measures of job enrichment such as task significance, skill variety, and autonomy have positive significant relationship on the employee satisfaction. The researcher also recommends that fast food restaurants should increase task significance among the workforce that could stimulate employee satisfaction and organizational performance.